STRUKTUR KEPRIBADIAN DAN MEKANISME PERTAHANAN EGO TOKOH UTAMA DALAM NOVEL WIGATI: LINTANG MANIK WORO KARYA KHILMA ANIS - Sutardi Sutardi; Hendrik Furqon; Alfina Nisa’Ur Rokhmah; Lady Lina Aulia (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study was to describe the personality structure of the main character in the novel Wigati:Lintang Manik Woro by Khilma Anis and to describe the ego defense mechanism of the main character in the novel Wigati:Lintang Manik Woro by Khilma Anis. The research method used is a qualitative research type, with a psychological approach and descriptive analysis method. The results of this study are that in Wigati, the forms of Id are found in the form of the desire to live in peace, avoid pain, and the desire to meet her biological father. In Manik¸, the form of Id is found in the form of great curiosity, interest in the opposite sex, and the desire to live with Hidayat Jati. The ego that emerged from Wigati's character was choosing to live in a boarding school¸ refusing to meet his biological father¸ looking for the whereabouts of his biological father. Manik's character is finding out about Wigati¸ approaching Hidayat Jati. The superego that appears in Wigati is Realizing that her abilities must be maintained properly, Realizing mistakes and Accepting her biological father. Pada Manik Realizes that there is no need to interfere too much in Wigati's affairs, Realizes that he should refrain from meeting Hidayat Jati¸ and Realizes that he is not worthy of being with Hidayat Jati. The ego defense mechanism in Wigati's character is Sublimation, Projection, Aggression, and Apathy. Meanwhile, in Manik's character, ego defense mechanisms are found in the form of projection and fantasy.